SENYAWA TRITERPENOID DARI EKSTRAK N-HEKSANA KULIT BATANG GARCINIAPICORRHIZA MIQ. - Soemiati, Atiek (UI Scholars Hub, 2005)
Triterpenoids from n-hexane extract of Garcinia picrorrhiza Miq. stem bark. Chromatographic separation of n-hexane extract of dried Garcinia picrorrhiza Miq. stem bark (Cluciaceae) furnished two triterpenoids, identified as 3oxo-7,24-euphadien-26oic acid (1), 3β-hydroxy-7,24-euphadien-26 oic acid (2). The structure of compounds were determined by using UV-vis, FT-IR, 1D and 2D NMR techniques.